Prediksi Erosi Guna Penerapan Metode Konservasi Tanah Dan Air Pada Aktivitas Pertanian Daerah Lereng Warmare - Isak Febian Rumpaidus; Yohanes Sriyadi Budiyanto; Rudolf Kristian Tukayo (Fakultas Pertanian Universitas Papua, 2015)
The objective of this study was to determine the rate of soil erosion occuring at the slope area of Warmare and the improvement needed to support sustainable farming activities without causing major risk to the enviroment and human safety. The research was conducted with soil survey techniques and descriptions of soil survey results and land evaluation. Data analysis is done by tabulation. Slope farming system were planned after knowing the potential and constrain based on the prediction of erosion rate done by using Universal Soil Loss Equation (USLE) equation. The results found that the actual land erosion rates of the slope area at Warmare for each SPT: SPT 1 (56.24 tons/ha/year) for secondary forest area, SPT 2 (2552.63 tons/ha/year) for cultivated area, SPT 3 (2325,03 tons/ha/year) for ex-shifting cultivated area, and SPT 4 (9.88 tons/ha/year) for secondary forest area. The main trigger factor for the increasing of soil erosion rate in some SPT were slope and length of slope, and agricultural activities without conservation practices. The improvement techniques that need to be done to support a sustainable agriculture practices in the slope area is the application of soil and water conservation methods with the following stages: (1) The restoration of the slope area with the modification of slope length and slope level by using mechanical technique such as contour cultivation, rorak, and Vertical mulch application, (2) ground surface protection from destruction of rain granules and surface runoff as well as soil properties restoration by using vegetative methods; and (3) collaboration of cultivation techniques by using agronomic methods.